Methodology for quality analysis of Regional Bathymetric Surfaces: From Brazilian South Coast to Hunter Channel - Florentino, LCDR C.; Pimentel, LCDR V.B.; Neto, A. (The International Hydrographic Review, 2019)
There are several projects looking for a better way to represent large areas of seabed mapping using Digital Terrain Models (DTMs). Nonetheless, the selection of a DTM becomes a challenge in which the result should reflect the model with the highest quality. Thus, this paper aims to promote the development of a methodology in order to apply a set of graphical and statistical tools capable of supporting quantitative and qualitative analysis by the comparison of one surface (called LEPLAC Sul) against other DTMs available (as ETOPO1 and GEBCO_2014) and against a bathymetric control data derived from hydrographic surveys. The outcomes show that LEPLAC Sul has achieved the highest index of quality, presenting itself as an efficient reference for further national scientific researches of middle scale, like those related to oceanographic and geomorphological modeling.